Pengaruh Effleurage Massage dan Teknik Relaksasi Nafas dalam terhadap Nyeri Punggung Bawah Ibu Hamil Trimester III - Ulfa Nur Azizah; Rinda Intan Sari; Diffa Risqa Arisdiani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Lower back pain is a common complaint among pregnant women in the third trimester. It is estimated that approximately 70% of pregnant women experience some form of back pain during pregnancy, childbirth, or postpartum. Non-pharmacological therapies such as deep breathing relaxation techniques and effleurage massage therapy can effectively reduce pain levels in these women. This study employs a quantitative approach using a quasi-experimental research method and employs purposive sampling with a sample size of 37 participants. Data analysis includes both univariate and bivariate analyses. Most respondents (64.9%) were aged between 20 and 35 years old. Additionally, the majority (64.9%) were experiencing their first pregnancy. All respondents (100%) were confirmed to have no comorbidities. Furthermore, 73% of the participants had tertiary education (Diploma, Bachelor's, Master's, or Doctorate degrees), and 62.2% continued working during pregnancy. The results of the Wilcoxon test indicated a significant effect (p = 0.000 < 0.05), confirming that effleurage massage and deep breathing relaxation techniques effectively reduce lower back pain in pregnant women. This reduction is attributed to the stimulation of tactile fibers in the skin by effleurage massage, which inhibits pain signals. In conclusion, the findings suggest that implementing effleurage massage and deep breathing relaxation techniques is beneficial for alleviating lower back pain in pregnant women. Public health advice advocates for the application of these techniques to manage such pain effectively.